2022
DOI: 10.3390/endocrines3030031
|View full text |Cite
|
Sign up to set email alerts
|

The Old and the New in Subacute Thyroiditis: An Integrative Review

Abstract: Subacute thyroiditis (SAT) is the most common cause of neck pain and thyrotoxicosis. Although this disease was recognized already by the end of the 18th century, new concepts regarding pathogenesis have emerged in recent years. Moreover, in the last two years, literature on SAT has increased significantly due to articles describing the possible connection with coronavirus disease 2019 (COVID-19). This integrative review depicts old and new concepts of this disease, proposing a detailed overview of pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 155 publications
(209 reference statements)
0
7
0
1
Order By: Relevance
“…Although no HLA testing was performed on any of the cases we reviewed, Stasiak et al. suggest that the presence of novel high-risk alleles, including HLA-B*18:01 and HLA-DRB1*01 , may deteriorate the clinical course of SAT ( 62 , 63 ). Another hypothesis involves molecular mimicry; a recent in-vitro investigation revealed that antibodies against SARS-CoV-2 antigens may cross-react with self-tissue antigens, such as TPO.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although no HLA testing was performed on any of the cases we reviewed, Stasiak et al. suggest that the presence of novel high-risk alleles, including HLA-B*18:01 and HLA-DRB1*01 , may deteriorate the clinical course of SAT ( 62 , 63 ). Another hypothesis involves molecular mimicry; a recent in-vitro investigation revealed that antibodies against SARS-CoV-2 antigens may cross-react with self-tissue antigens, such as TPO.…”
Section: Discussionmentioning
confidence: 98%
“…As this theory states, HLAmediated tissue destruction occurs through either cross-reaction with host antigens or auto-antibody formation against the large amount of self-antigens released from the damaged thyroid tissue. Although no HLA testing was performed on any of the cases we reviewed, Stasiak et al suggest that the presence of novel high-risk alleles, including HLA-B*18:01 and HLA-DRB1*01, may deteriorate the clinical course of SAT (62,63). Another hypothesis involves molecular mimicry; a recent in-vitro investigation revealed that antibodies against SARS-CoV-2 antigens may cross-react with selftissue antigens, such as TPO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TG is involved in the formation of thyroid hormones (T3 and T4) 90 . Elevated TG, T3, and T4 levels from ruptured follicles cause thyrotoxicosis in patients 91 . TSH is suppressed by a negative feedback loop of elevated thyroid hormones, 92 and symptoms of hyperthyroidism occur.…”
Section: Subacute Thyroiditis After Covid‐19 Infectionmentioning
confidence: 99%
“…90 Elevated TG, T3, and T4 levels from ruptured follicles cause thyrotoxicosis in patients. 91 TSH is suppressed by a negative feedback loop of elevated thyroid hormones, 92 and symptoms of hyperthyroidism occur. Before the euthyroid state, FT3 and FT4 decrease, and TSH increases moderately prompting hypothyroidism symptoms.…”
Section: Subacute Thyroiditis After Covid-19 Infectionmentioning
confidence: 99%